Isolation and identification of bioactive substance 1‐hydroxyphenazine from Pseudomonas aeruginosa and its antimicrobial activity. (1st September 2020) - Liu, T.T.; Ye, F.C.; Pang, C.P.; Yong, T.Q.; Tang, W.D.; Xiao, J.; Shang, C.H.; Lu, Z.J.
Abstract: A strain named as Pseudomonas aeruginosa 2016NX1, which could produce phenazine and cereusitin, was isolated from the root of Millettia specisoa . Phenazines were extracted, isolated and purified by chloroform, thin‐layer chromatography, column chromatography and high‐performance liquid chromatography. Then the purified materials were identified by analysis of nuclear magnetic resonance. The major yellow component is 1‐hydroxyphenazine and the minor blue component is cereusitin A. The tests of antimicrobial activity of yellow component showed that the growth of several common plant pathogenic fungi and bacteria (such as Cochliobolus miyabeanus, Diaporthe citri, Salmonella sp., Klebsiella oxytoca ) could be strongly inhibited. This study suggested that Pseudomonas aeruginosa strain 2016NX1 had a significant potential for biological control of phytopathogenic fungi. Significance and Impact of the Study: In this study, one bioactive substance from Pseudomonas aeruginosa 2016NX1 was identified and its antimicrobial activity was verified. This study demonstrated that one bioactive substance from P. aeruginosa can strongly inhibit the growth of plant pathogenic fungi and bacteria. This study suggested that P. aeruginosa strain 2016NX1 has a significant potential for biological control of phytopathogenic fungi.